Nanoengineered Drug Delivery Systems for Enhancing Antibiotic Therapy. Issue 3 (24th December 2014) - Kalhapure, Rahul S.; Suleman, Nadia; Mocktar, Chunderika; Seedat, Nasreen; Govender, Thirumala
<x xml:space="preserve">Abstract</x> Formulation scientists are recognizing nanoengineered drug delivery systems as an effective strategy to overcome limitations associated with antibiotic drug therapy. Antibiotics encapsulated into nanodelivery systems will contribute to improved management of patients with various infectious diseases and to overcoming the serious global burden of antibiotic resistance. An extensive review of several antibiotic‐loaded nanocarriers that have been formulated to target drugs to infectious sites, achieve controlled drug release profiles, and address formulation challenges, such as low‐drug entrapment efficiencies, poor solubility and stability is presented in this paper. The physicochemical properties and the in vitro/in vivo performances of various antibiotic‐loaded delivery systems, such as polymeric nanoparticles, micelles, dendrimers, liposomes, solid lipid nanoparticles, lipid–polymer hybrid nanoparticles, nanohybirds, nanofibers/scaffolds, nanosheets, nanoplexes, and nanotubes/horn/rods and nanoemulsions, are highlighted and evaluated. Future studies that will be essential to optimize formulation and commercialization of these antibiotic‐loaded nanosystems are also identified. The review presented emphasizes the significant formulation progress achieved and potential that novel nanoengineered antibiotic drug delivery systems have for enhancing the treatment of patients with a range of infections. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:872–905, 2015